The Influence of Cr doping on the Structural and Magnetic Properties of HoMnO3 Multiferroic Ceramics - (:unkn) unknown (IOP PUBLISHING LTD, 2019)
In this research single-phase Cr-doped HoMnO3 ceramics were synthesized via solid state reaction method. The structural and magnetic characteristics of the prepared samples were examined using various characterization techniques, including x-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDX) and vibrating sample magnetometer (VSM). All samples exhibit single phase that emphasized by SEM and XRD. Magnetic properties of the prepared samples at low temperature (10K) showed the presence of different magnetic characteristics. The change in magnetic behavior could probably occur due to slight decrease in the unit cell volume that leads to a structural distortion in the lattice. Cr-doped HoMnO3 could be a good candidate with a better ferromagnetic property for practical multiferroic applications.
Keywords: ELASTICITY; STRENGTH; POROSITY; ALUMINA